Epigenetics modification among vitrified oocytes and early embryos derived from them: a narrative review: Epigenetics modification of oocytes and embryos - Saeedinia, Mostafa; Chen, Jiayi; Kohandel Gargari, Omid; Jafarabady, Kyana; Zaki-Dizaji, Majid; Ghorbankhanloo , Alireza; Heidary, Zohreh (Cellular and Molecular Biology, 2024)
Vitrification has important application in assisted reproductive technology (ART) and this technique has been widely used in the cryopreservation of oocytes and embryos. However, due to susceptibility of epigenetic modifications to environmental changes induced by cryopreservation procedures, there are concerns about the potential epigenetic consequences of oocyte and embryo vitrification. This review comprehensively summarized the effect of cryopreservation—especially the vitrification method in ART-on oocytes and embryos. Various studies have reported changes in different aspects of genomic status which directly affect the quality of fertilized embryos. The objective of this review is to assess existing literature on the epigenetic modifications that occur in vitrified oocytes and early embryos resulting from oocyte vitrification, including DNA modifications, RNA methylation, histone modification and microRNAs related to ART.